Solve for t -t=9(t-10)

Math
-t=9(t-10)
Simplify 9(t-10).
Tap for more steps…
Apply the distributive property.
-t=9t+9⋅-10
Multiply 9 by -10.
-t=9t-90
-t=9t-90
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 9t from both sides of the equation.
-t-9t=-90
Subtract 9t from -t.
-10t=-90
-10t=-90
Divide each term by -10 and simplify.
Tap for more steps…
Divide each term in -10t=-90 by -10.
-10t-10=-90-10
Cancel the common factor of -10.
Tap for more steps…
Cancel the common factor.
-10t-10=-90-10
Divide t by 1.
t=-90-10
t=-90-10
Divide -90 by -10.
t=9
t=9
Solve for t -t=9(t-10)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top